Magnesium Disorders and Prognosis in Heart Failure: A Systematic Review. Issue 6 (12th May 2021) - Voultsos, Petros; Bazmpani, Maria-Anna; Papanastasiou, Christos A.; Papadopoulos, Christodoulos E.; Efthimiadis, Georgios; Karvounis, Haralambos; Kalogeropoulos, Andreas P.; Karamitsos, Theodoros D.
Abstract : Magnesium is an essential mineral for the human body and plays an important role in cardiovascular health. Hypomagnesaemia has been linked with increased cardiovascular mortality in heart failure; however, previous studies have yielded conflicting results. Even fewer studies have addressed the association between hypermagnesemia and prognosis in heart failure. The aim of the present systematic review was to investigate the association of serum magnesium levels with cardiovascular and all-cause mortality in patients with heart failure and reduced ejection fraction (HFrEF). Cardiovascular morbidity, referring to heart failure rehospitalizations and ventricular arrhythmias, was also investigated. Eligible studies were identified by searching PubMed and Scopus. The Quality in Prognosis (QUIPS) tool was used to assess the quality of included studies. Eight studies (total of 13, 539 patients with HFrEF) that assessed the effects of serum magnesium levels on cardiovascular mortality, all-cause mortality, and cardiovascular morbidity met inclusion criteria. In half of the studies, hypomagnesemia was found to be an independent risk factor for cardiovascular mortality, including sudden cardiac death. Only 1 study reported that hypermagnesemia (serum magnesium levels above 2.4 mg/dL) is a prognostic factor for noncardiac mortality suggesting that hypermagnesemia is more likely an indicator of comorbidities rather than a true independent prognostic marker. Finally, low serum magnesium levels were not associated with readmissions for heart failure or ventricular arrhythmias in patients with HFrEF.